Canada’s Education System: Policies & Challenges During the COVID-19 Pandemic. An Interview With Dr. Charles Ungerleider - Arfaie, Saman; Glinos, Peter; Honarvar, Faraz (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2022)
This work is a scholarly interview conducted with Dr. Charles Ungerleider on the effects of COVID-19 in Canada. The discussion explores the various aspects of the pandemic’s impact on Canadian education, such as: the effects of school closures; Canada’s lack of a federal ministry of education; the burnout faced by educators resulting from the sudden shift to online education; the obstacles in educating international students; the reduction of experiential learning in post-secondary schools; the media’s portrayal and politicization of pandemic school closures; the forced integration of virtual learning technology; the disproportionately deleterious repercussions of the pandemic education on the marginalized; and the need for schools in creating social cohesion.